Comunicazione istituzionale e prospettive di genere: Uno studio sul social posting delle Regioni italiane, fra regole e pratiche - D'Ambrosi, Lucia; Ducci, Gea; Folena, Camilla; Spalletta, Marica (Mediascapes journal, 2024)
Over the past few years, marked by issues and activism from feminists, women's movements, and the LGBTQ+ community, there has been increasing attention in the public discourse on gender-sensitive policies, advocating for a more ethical and responsible dimension of public sector communication. In Italy, the focus on gender issues in public sector communication strategies has been slow to emerge, often remaining barely visible. However, particularly during the pandemic, gender studies in public sector communication have intensified, partly due to pressure from engaged citizens. Significant emphasis has been placed on promoting non-discriminatory and gender-sensitive language in institutional recommendations and local guidelines, with various initiatives implemented by municipalities and regions aiming to enhance women's identity in public sector communication and counter stereotypical and discriminatory representations. The paper presents the findings of a pilot study addressing gender perspectives in public sector communication by examining the complex dynamics between rule adoption, the tendency to replicate established practices, and the development of a creative dimension in communication strategies. The research focuses on selected Italian regions and investigates their communication practices through official Facebook accounts, analyzing verbal, visual, and audio-visual languages. The study's findings confirm the delicate balance between the rules governing gender-sensitive approaches and their manifestation in communication practices, influenced by the creative variable and the empowerment of public communication professionals. Additionally, the research aims to test a methodology that can be replicated in other regions or local contexts, potentially facilitating comparative analyses.